(untitled) (Revista de Artes Marciales Asiáticas, 2016)
Persian archery manuals provide lots of useful information on shooting with a Persian composite bow. The main aim of this article is to provide, for the first time, a full annotated translation of an undated Persian archery manual written by Mohammad Zaman known as Ceraq Beg from the family of Kamran Beg Qaranaj. The manual is handwritten and consists of twenty four pages which include twelve chapters. Despite the occasional confusion, the obscure vocabulary, and the odd clumsy description, the text is a mine of information. It shows the continuity of the Persian archery tradition at least to the end of the eighteenth century and increases our knowledge of some of the details once commonplace that are now obscure. The gradual increase in our knowledge of Persian archery is progressing through the discovery and translation of works like this one of Mohammad Zaman. Such manuals introduce new techniques and also confirm the pervasiveness of the basic forms of this ancient art.